PENGEMBANGAN MEDIA PEMBELAJARAN BERBENTUK BUKU SAKU DI KELAS X SMA NEGERI I AMANUBAN TIMUR TAHUN AJARAN 2021/2022 - Oryanti, Selan; Samin, Mikael; H. N. Mari, Natalia Adel (Jurnal Geografi, 2023)
The purpose of this research is to produce a development product in the form of an Earth pocket book as a living space in SMA Negeri 1 Amanuban Timur class X. The development model used is the ADDIE Model. The data instrument used by the researcher is a questionnaire. The data analysis technique used by the researcher is quantitative descriptive analysis. The results obtained from the validation test in terms of material obtained 92.5%, validation test in terms of language obtained 92.85%, in terms of media obtained 92.64% with good qualifications. The percentage of small group test assessments and large group tests obtained 91.87% and 89.56% with good qualifications and it can be judged that the development of the Earth pocket book media as a living space received a positive response and the total percentage of material, language, media, and academic experts large groups and small groups, namely 87.69%. In addition, in terms of material, the suitability of the material and the pocket book supports each other, in terms of language the use of sentence structures, and in accordance with the rules of writing interesting language so that it becomes the basis for students' attention to see the pocket book, and from a media perspective, the physical appearance of the Earth pocket book as a living space looks simple but practical. then the pocket book of the Earth as a living space is said to be feasible. The conclusion from this study is that the Earth pocket book as a proper and valid living space is used as a learning medium at SMA Negeri I Amanuban Timur for the Academic Year 2021/2022.